1997
DOI: 10.1089/dna.1997.16.111
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of the Rat Somatostatin Receptors: Subtype Discrimination, Ligand Specificity, and Delineation of Carboxy-Terminal Positive and Negative Sequence Motifs

Abstract: Endocytosis of the five rat somatostatin receptor subtypes (SSTR1-5) was investigated in transfected HEK cells by biochemical ligand binding assays and confocal microscopic analysis. Phenylarsine oxide-sensitive internalization of SSTR1-3 is dependent on SST-14 or SST-28, whereas only the octacosapeptide triggers this reaction with SSTR5. SSTR4 is not internalized with either SST. Internalized SSTR3 is cycled back to the plasma membrane while endocytosed rho-Ala1-SST-14 remains inside the cell. Delineation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 25 publications
7
97
0
Order By: Relevance
“…Numerous mutagenesis studies have demonstrated that phosphorylation of serine and threonine residues in the Cterminal tail initiates receptor-mediated endocytosis (15,16,18,19). Nine putative S/T phosphorylation sites are deleted by the vl mutation (ca.expasy.org; McVector version 9.0), consistent with our endocytosis phenotype.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Numerous mutagenesis studies have demonstrated that phosphorylation of serine and threonine residues in the Cterminal tail initiates receptor-mediated endocytosis (15,16,18,19). Nine putative S/T phosphorylation sites are deleted by the vl mutation (ca.expasy.org; McVector version 9.0), consistent with our endocytosis phenotype.…”
Section: Discussionsupporting
confidence: 77%
“…Gpr161 is expressed at all examined stages of lens development: lens pit (E10.5), lens vesicle (E11.5), primary lens Vl Mutation Affects Gpr161 Receptor-Mediated Endocytosis. Receptor-mediated endocytosis is a common mechanism by which GPCR signaling is attenuated and is regulated by C-terminal tail phosphorylation (15,16,18,19). To investigate the effects of the mutation on Gpr161 plasma membrane targeting and intracellular localization, WT and vl-myc-Gpr161 constructs were transfected into HEK293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…SSTR5 was able to inhibit only the early phase of enzyme activation, allowing the late phase to occur unencumbered. From the literature, it appears that there are di¡er-ences in the cellular regulation of the ¢ve SSTRs and a di¡er-ent pattern of internalization has been described for each of them [12,13]. One can hypothesize that in our cells SSTR5 receptors may undergo a desensitization and internalization faster than the other two subtypes thus preventing a longterm action.…”
Section: Discussionmentioning
confidence: 80%
“…All polyclonal rabbit antisera were purified by affinity chromatography using the Sulfo-Link coupling gel coupled to the appropriate immunizing peptide according to the instructions of the manufacturer (Pierce). Plasmid constructs of the rat sst 1 , sst 2A , sst 3 , sst 4 , and sst 5 containing the amino-terminal T7 epitope tag sequence MASMTGGQQMG in pcDNA3 have been described previously (13,15,21). Truncated sst 2A mutants were created by PCR using primers that introduce stop codons at suitable positions (22).…”
Section: Methodsmentioning
confidence: 99%
“…the rat sst 4 receptor appears to be largely resistant to agonist-induced internalization and desensitization (13), whereas the human sst 4 receptor has been reported to undergo a very slow but clearly detectable endocytosis. Other studies have shown that the human sst 1 receptor but not the rat sst 1 receptor failed to internalize in an agonist-dependent manner (14,15).…”
mentioning
confidence: 93%